2019
DOI: 10.1097/phh.0000000000000790
|View full text |Cite
|
Sign up to set email alerts
|

In-Home Secondhand Smoke Exposure Among Urban Children With Asthma: Contrasting Households With and Without Residential Smokers

Abstract: In-home SHS exposure remains alarmingly high in urban environments. However, a substantial proportion of this exposure appears to be occurring only from external sources that enter the home. Caregivers in these homes had higher desire but lower agency to avoid SHSe, driven by lack of functional support and physical isolation. Public policies targeting these factors may help remediate exposure in this especially vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…43 Children living in US urban centers are at risk for secondhand smoke exposure as multiple studies have found ≥50% of urban children are exposed to SHS. 10,[44][45][46] This percentage is higher than expected, as currently 12.4% of US adults and 8.1% of US adolescents are active smokers, 47 illustrating both higher rates of tobacco use and overcrowding in urban households. Moreover, persons living in poverty, children under age 11, non-Hispanic Blacks, persons living in rental housing, and those with less than a high school education are more likely to be exposed to SHS.…”
Section: Indoor and Outdoor Urban P Ollutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Children living in US urban centers are at risk for secondhand smoke exposure as multiple studies have found ≥50% of urban children are exposed to SHS. 10,[44][45][46] This percentage is higher than expected, as currently 12.4% of US adults and 8.1% of US adolescents are active smokers, 47 illustrating both higher rates of tobacco use and overcrowding in urban households. Moreover, persons living in poverty, children under age 11, non-Hispanic Blacks, persons living in rental housing, and those with less than a high school education are more likely to be exposed to SHS.…”
Section: Indoor and Outdoor Urban P Ollutantsmentioning
confidence: 99%
“…Children living in US urban centers are at risk for secondhand smoke exposure as multiple studies have found ≥50% of urban children are exposed to SHS 10,44–46 47 illustrating both higher rates of tobacco use and overcrowding in urban households.…”
Section: Indoor and Outdoor Urban Pollutantsmentioning
confidence: 99%
“…Starting from this evidence, in the present study, we analysed NGF and its receptors in a group of non-smokers, adult volunteers exposed to short-term SS in a controlled home-like environment [ 27 , 44 ]. Determination of cotinine levels in urine samples was used as the classical, standard biomarker of SS exposure, as described in the literature [ 31 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Air nicotine concentration can be measured to assess SHS exposure in a specific environment [12]. Nicotine is specific to tobacco smoke and often used to evaluate SHS in different indoor settings [13][14][15]. The biomarker cotinine, a nicotine metabolite, can be used to determine individual SHS exposure.…”
Section: Introductionmentioning
confidence: 99%